Purification of Maize Nucleotide Pyrophosphatase/Phosphodiesterase Casts Doubt on the Existence of Zeatin Cis–Trans Isomerase in Plants - Hluska, Tomáš; Šebela, Marek; Lenobel, René; Frébort, Ivo; Galuszka, Petr (Frontiers in Plant Science, 2017)
Almost 25 years ago, an enzyme named zeatin cis trans isomerase from common bean has been described by Bassil et al. in Plant Physiol. (1993) 102: 867-872. The partially purified enzyme required an external addition of FAD and dithiothreitol for the conversion of cis-zeatin to its trans- isomer that occurred only under light. Although an existence of this important enzyme involved in the metabolism of plant hormones cytokinins was generally accepted by plant biologists, the corresponding protein and encoding gene have not been identified to date. Based on the original paper, we purified and identified an enzyme from maize, which shows the described zeatin cis trans isomerase activity. The enzyme belongs to nucleotide pyrophosphatase/phosphodiesterase family, which is well characterized in mammals, but less known in plants. Further experiments with the recombinant maize enzyme obtained from yeast expression system showed that rather than the catalytic activity of the enzyme itself, a non-enzymatic flavin induced photoisomerization is responsible for the observed zeatin cis trans interconversion in vitro. An overexpression of the maize nucleotide pyrophosphatase/phosphodiesterase gene led to decreased FAD and increased FMN and riboflavin contents in transgenic Arabidopsis plants. However, neither contents nor the ratio of zeatin isomers was altered suggesting that the enzyme is unlikely to catalyze the interconversion of zeatin isomers in vivo. Using enhanced expression of a homologous gene, functional nucleotide pyrophosphatase/phosphodiesterase was also identified in rice.